2021
DOI: 10.1021/acsaem.1c01493
|View full text |Cite
|
Sign up to set email alerts
|

Zeolitic Imidazole Framework Sacrificial Template-Assisted Synthesis of NiCoP Nanocages Doped with Multiple Metals for High-Performance Hybrid Supercapacitors

Abstract: Metal phosphides have great potential for electrochemical energy-storage devices and electrocatalysis. Although monometallic and bimetallic phosphides have been extensively studied, the preparation of more complex metal phosphides remains challenging and it is necessary to further expand the available design space. Herein, we report a universal method to dope various metal cations into NiCoP nanocages (M-NiCoP, M = Al, Cu, Cr, Zn). Interestingly, the method can also be expanded to allow the incorporation of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 68 publications
(122 reference statements)
0
13
0
Order By: Relevance
“…The standard SC was invented by Robert Rightmire, and credit for fabrication of the first commercial SCs in 1975 went to the Japanese company Nippon Electric Company. The electrode materials, electrolytes, and operation conditions are the main factors that determine the SC’s performance. , Transition metal-based electrode materials (TMEMs) are among the most promising electrodes for SCs, due to their relative stability, specific power, and quick charging/discharging rates. , Various transition metal-based oxides (TMOs), sulfides (TMSs), and phosphides (TMPs) have been developed for SCs. However, the low energy density, strong internal resistance, and low mechanical strength of TMEMs remain critical barriers precluding their utilization in practical SCs . The morphology and composition of TMEMs and the type of the electrolytes are the main factors that determine the SC’s performance .…”
Section: Introductionmentioning
confidence: 99%
“…The standard SC was invented by Robert Rightmire, and credit for fabrication of the first commercial SCs in 1975 went to the Japanese company Nippon Electric Company. The electrode materials, electrolytes, and operation conditions are the main factors that determine the SC’s performance. , Transition metal-based electrode materials (TMEMs) are among the most promising electrodes for SCs, due to their relative stability, specific power, and quick charging/discharging rates. , Various transition metal-based oxides (TMOs), sulfides (TMSs), and phosphides (TMPs) have been developed for SCs. However, the low energy density, strong internal resistance, and low mechanical strength of TMEMs remain critical barriers precluding their utilization in practical SCs . The morphology and composition of TMEMs and the type of the electrolytes are the main factors that determine the SC’s performance .…”
Section: Introductionmentioning
confidence: 99%
“…3e), it can be found that the oxidation/reduction peak shift to a higher/lower potential state along with the sweep speeds increasing owing to the polarization and ohmic resistance. 66 Simultaneously, the CV graphs still keep the well symmetrical and similar profile with the enhancement of the scanning speed, implying excellent reversibility and good rate capability. 65,66 Furthermore, the CV graphs of the as-fabricated electrodes from 10 to 100 mV s −1 are represented in Fig.…”
Section: Resultsmentioning
confidence: 79%
“…66 Simultaneously, the CV graphs still keep the well symmetrical and similar profile with the enhancement of the scanning speed, implying excellent reversibility and good rate capability. 65,66 Furthermore, the CV graphs of the as-fabricated electrodes from 10 to 100 mV s −1 are represented in Fig. S19.…”
Section: Resultsmentioning
confidence: 79%
“…19,20 The battery-like materials should possess copious electroactive sites for faradaic redox reactions, enough conductivity for effective charge transfer, a highly porous nature for rapid ion transport, and a high surface area for charge storage. 21 Among the various battery-like cathode materials, layered double hydroxides (LDHs) such as FeCo-LDH, 22 MnCo-LDH, 23 and NiCo-LDH 24 are the most promising candidates due to their several advantages such as good anion exchanging ability, good redox activities, environmental friendliness, superior anionexchanging ability, and low cost. 25 However, utilization of LDHs as cathode materials is still limited owing to their sluggish kinetics behavior, which leads to a low capacity and structural instability.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The battery-like materials should possess copious electroactive sites for faradaic redox reactions, enough conductivity for effective charge transfer, a highly porous nature for rapid ion transport, and a high surface area for charge storage. 21…”
Section: Introductionmentioning
confidence: 99%